A Computational Method for n-Dimensional Laplace Transforms Involved with Fourier Cosine Transform. (28th August 2013) - Saberi-Nadjafi, Jafar
Abstract : In 2007, the author published some results on n -dimensional Laplace transform involved with the Fourier sine transform. In this paper, we propose some new result in n -dimensional Laplace transforms involved with Fourier cosine transform; these results provide few algorithms for evaluating some n -dimensional Laplace transform pairs. In addition, some examples are also presented, which explain the useful applications of the obtained results. Therefore, one can produce some two- and three- as well as n -dimensional Laplace transforms pairs.